Segurança pública municipal: um estudo sobre a gestão do 2º batalhão de polícia militar frente o aumento da violência e redução do efetivo policial na cidade de Araguaína - TO - Silva, Hugo Martins Bruno (Universidade Federal do Tocantins, 2020)
The purpose of this study was investigate the way things happen in the 2nd Military Police Department - 2MPD, in face of the crime and constant cutback of the police officers in the city of Araguaina-TO, specifically had the intention of perform documentary survey, with the purpose of pointing the main incidences of crimes associates with the violence in the city of Araguaina-TO; Analyze how are developed the actions carried out by the 2nd MPD; and offer improvements, showing what’s working, from the research data, in order to improve the city environment in relation to public safety. Classifying the proceedings as a documentary investigation order, with approach qualitative, with ends of description and exploration. With the result of the research, were identify the growing 67,7% of crimes in the last 4 (four) years in the county of Araguaina, showing the apparent need of police officers addition, not only in the city, but in all the state of Tocantins, in order of the discrepancy of police officers in the state and the constant increase of violence.